2013
DOI: 10.1371/journal.pone.0079848
|View full text |Cite
|
Sign up to set email alerts
|

Association of HDL-Related Loci with Age-Related Macular Degeneration and Plasma Lutein and Zeaxanthin: the Alienor Study

Abstract: BackgroundSeveral genes implicated in high-density lipoprotein (HDL) metabolism have been reported to be associated with age-related macular degeneration (AMD). Furthermore, HDL transport the two carotenoids, lutein and zeaxanthin, which are highly suspected to play a key-role in the protection against AMD. The objective is to confirm the associations of HDL-related loci with AMD and to assess their associations with plasma lutein and zeaxanthin concentrations.MethodsAlienor study is a prospective population-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 49 publications
2
33
1
Order By: Relevance
“…Also, there were two studies which have got opposite results and proved significant association between LIPC (rs493258) and AMD development [26,27]. It should be noted, that we are in agreement with these six studies [11,12,18,19,21,22], which found that LIPC gene polymorphisms (rs10468017, rs493258) may reduce possibility for AMD development. Reynolds et al investigated 458 participants study, including 318 advanced AMD cases with either geographic atrophy (n=123) or neovascular AMD (n=195), and 140 controls [12].…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Also, there were two studies which have got opposite results and proved significant association between LIPC (rs493258) and AMD development [26,27]. It should be noted, that we are in agreement with these six studies [11,12,18,19,21,22], which found that LIPC gene polymorphisms (rs10468017, rs493258) may reduce possibility for AMD development. Reynolds et al investigated 458 participants study, including 318 advanced AMD cases with either geographic atrophy (n=123) or neovascular AMD (n=195), and 140 controls [12].…”
Section: Discussionsupporting
confidence: 87%
“…Our results showed a protective role of these three gene polymorphisms: LIPC rs10468017 polymorphism decreased risk of both forms of AMD (early and exudative), LIPC rs493258 polymorphism decreased risk only of Regarding the results analyzing LIPC gene polymorphisms association with AMD, six studies found that LIPC gene can slow down AMD development [11,12,18,19,21,22]. Among these six studies, two studies analyzed LIPC (rs10468017) gene polymorphism [12,21] and three LIPC (rs493258) [11,18,22], while one study analyzed both gene polymorphisms [19]. Four studies found no association with AMD [16,17,23,24], two studies analyzed only rs10468017 polymorphism association with AMD [16,17] and two other studies analyzed both LIPC gene polymorphisms [23,24].…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations